A systematic review on the impact of SARS-CoV-2 viral infection on precocious puberty - Ghooli, Indu; Jorige, Archana (International Journal of Contemporary Pediatrics, 2024)
Precocious puberty is defined as the onset of sexual characteristics before age 8 in girls and 9 in boys, with serious physical and psychological implications, including advanced bone maturation, early growth cessation, and increased behavioral issues. As per the studies done by Gupta et al precocious puberty cases have risen during the pandemic, prompting inquiries into the potential link between SARS-CoV-2 and early pubertal onset. PubMed, Scopus Web of Science, Google Scholar, and other electronic databases were used for the literature search. The search was restricted to studies published between January 2020 and July 2024. The study has shown a concerning increase in precocious puberty cases during the pandemic, with reports of a significant rise ranging from 9.8% to 93%. The increase clearly shows the concern of having a massive impact on the puberty timing in girls. The data reveal a consistent increase in the incidence of precocious puberty during the pandemic, with relative increases ranging from 0.2 average incidence per month pre-pandemic to 5.9 average per month pandemic incidence. These findings underscore the need for localized public health strategies and further research to fully understand the long-term implications of early puberty in the context of the COVID-19 pandemic. This review emphasizes the importance of continued monitoring and research to mitigate the potential long-term health risks associated with precocious puberty, including metabolic, cardiovascular, and psychological disorders.